2013
DOI: 10.4236/ojrm.2013.23012
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a mouse model of collagen antibody-induced arthritis with human adipose-derived secretions

Abstract: The use of adipose-derived cells as a treatment for a variety of diseases is becoming increasingly common. These therapies include the use of cultured mesenchymal stem cells (MSCs) and freshly isolated stromal vascular fraction (SVF) alone, or in conjunction with other cells such as adipocytes. There is a substantial amount of literature published on the therapeutic properties of MSCs and their secretions as the main driver of their therapeutic effect. However, there is little data available on the therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…However, differentiation is not the primary mode of action and in vitro animal models and human data have demonstrated that a complex set of secretions drive the anti-inflammatory and regenerative effects that have been observed [ 29 ]. Thus, the secretome of MSCs has become of particular interest and multiplex cytokine analyses are used to assess cell populations and the “cytokine profile” is predictive of in vivo effect [ 30 ]. Proinflammatory cytokines such as Interleukin-1 β (IL-1 β ) play a pivotal role in the pathogenesis of OA.…”
Section: Introductionmentioning
confidence: 99%
“…However, differentiation is not the primary mode of action and in vitro animal models and human data have demonstrated that a complex set of secretions drive the anti-inflammatory and regenerative effects that have been observed [ 29 ]. Thus, the secretome of MSCs has become of particular interest and multiplex cytokine analyses are used to assess cell populations and the “cytokine profile” is predictive of in vivo effect [ 30 ]. Proinflammatory cytokines such as Interleukin-1 β (IL-1 β ) play a pivotal role in the pathogenesis of OA.…”
Section: Introductionmentioning
confidence: 99%